The influence of supportive leadership on hospitality employees’ green innovative work behavior: the mediating role of innovative climate and psychological empowerment - Arif Jameel; Noman Sahito; Wenjing Guo; Abid Hussain; Shahida Kanwel; Sania Khan (Frontiers in Psychology, 2025)
IntroductionHighlighting the implications of supportive leadership, the research examines the role of supportive leadership in predicting employee green and innovative work behaviors. The study also analyzes the mediating effect of innovative climate and psychological empowerment on the relationship between supportive leadership and green innovative work behavior.MethodsThe data was gathered from full-time workers and managers employed at hotels in Saudi Arabia and analyzed using SPSS and AMOS. A study was conducted on a sample comprising 372 dyads of workers and their immediate supervisors.ResultsThe findings indicated that supportive leadership had a favorable correlation with green innovative work behavior, which was mediated by innovative climate and psychological empowerment among hotel employees. This study enhances the green innovative work behavior theory by identifying key psychological and organizational factors that motivate employees to engage in environmentally friendly activities within the hospitality industry.ConclusionThis research offers theoretical insights, practical applications, and suggestions for hospitality industry management.